Islamic Education Transformation at Nurul Jadid University: The Controversy of Pesantren Values and Global Academia - Misbahul Arifin (DAAR EL-MAKRIFAH: Journal of Islamic Religious Education, 2026)
This study focuses on the integration of pesantren values into the academic system of Nurul Jadid University as a model of Islamic higher education in addressing the challenges of globalization. The research aims to explore how the identity of pesantren can be preserved without neglecting modern academic demands, while at the same time discovering a balanced model between tradition and modernity in higher education management. The study employs a qualitative method with a case study approach. Data were collected through in-depth interviews, observations, and documentation at Nurul Jadid University, KH. Zaini Mun’im Street, Karanganyar, Paiton, Probolinggo in August 2025. Data analysis was conducted through thematic reduction, presentation, and verification. The findings reveal that integrating pesantren values into the academic system presents challenges, such as the potential dichotomy between tradition and modernity, but also opens opportunities through the strengthening of contextual curriculum, institutional culture, and adaptive use of digital technology. The implications of this study highlight that Islamic higher education based on pesantren can create a balanced integration model, thus maintaining the spiritual essence of Islam while simultaneously enhancing global competitiveness.